Pengaruh Konsentrasi Madu dalam Menghambat Pertumbuhan Staphylococcus Aureus - Nardin Nardin (Jurnal Media Laboran, 2017)
This study aims to determine how much the ability of honey used as a sample can inhibit the growth of Staphylococcus aureus. This research was conducted by laboratory experiment by testing Honey Concentration Effect in Staphylococcus aureus Growth by using concentration: 5%, 10%, 15%, 20%, and 25%. This research was conducted at GG Clinic of Makassar City. The population in this study was honey and the samples in this study were honey with dilution of 5% v / v, 10% v / v, 15% v / v, 20% v / v, and 25% v / v. The independent variable in this study is the concentration of honey while the dependent variable in this research is the growth barrier area of ​​Staphylococcus aureus. From the results of this study showed that honey with dilution can not inhibit the growth of Staphylococcus aureus